2021
DOI: 10.1371/journal.pone.0254258
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of underlying diseases on the prognosis of patients with COVID-19

Abstract: Underlying diseases might be risk factors for poor prognosis in patients with coronavirus disease (COVID-19); however, we still do not know whether these diseases are independent factors affecting prognosis, which type of underlying diseases are risk factors, and which type of clinical outcomes are affected. We retrospectively reviewed cohort data from 7,590 de-identified patients with COVID-19 who were diagnosed using severe acute respiratory syndrome-coronavirus-2 RNA polymerase chain reaction test up to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Our findings are consistent with the current literature, where the majority of poor outcomes are noted among the older populations ( 3 , 8 , 25 ) and individuals with underlying conditions ( 6 ). A model based on age and other clinical variables predicted death among COVID-19 patients in China ( 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with the current literature, where the majority of poor outcomes are noted among the older populations ( 3 , 8 , 25 ) and individuals with underlying conditions ( 6 ). A model based on age and other clinical variables predicted death among COVID-19 patients in China ( 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, the morbidity and mortality of Category A and B are used to reflect the spread of infectious diseases. The morbidity and mortality of Category A and B infectious diseases are significantly different from the population mortality ( 2 ), life expectancy per capita ( 3 ), newborn mortality ( 4 ), and prevalence of underlying diseases ( 5 , 6 ) in the previous literatures. The former belongs to infectious diseases, which have the characteristics of “human-to-human transmission.” It is more easily to measure the spread of infectious diseases.…”
Section: Introductionmentioning
confidence: 94%
“…Underlying diseases might be risk factors for poor prognosis in patients with COVID-19 infection. Current knowledge has shown that death rate is high in people with chronic underlying diseases [27], [28]. In our study, 989 patients (79,5%) had no underlying diseases, while 12,6% had an underlying disease, such as hypertension, cardiovascular diseases, diabetes mellitus, malignancy, and chronic kidney disease.…”
Section: B Logistic Regression For the Rt-pcr For Sars-cov-2 Test Res...mentioning
confidence: 56%